Evaluation of cold shock resistant spermatozoa of buffalo bull through polyacrylamide gel migration - SINGH, SATWINDER; PANGAONKAR, G R; SINGH, JAGIR (The Indian Journal of Animal Reproduction, 2023)
The initial motility, live percentage in normal spermatozoa decreased due to cold shock. The cold shock treatmentaffected adversely the penetrability of spermatozoa through polyacrylamide gel column.
Keywords: Buffalo spermatozoa; PAGE; cold shock